CP-110 Multidisciplinary views towards the clinical pharmacist: a hospital palliative care team perspective. (25th February 2017) - Atkins, SR; Cunningham, S; West, LM
Abstract : Background: Successful provision of palliative care requires multidisciplinary collaboration from various healthcare professionals. 1 Purpose: To explore the views of the multidisciplinary healthcare team towards the role of the clinical pharmacist within the palliative care unit of an oncology hospital. Material and methods: Open ended and close ended questions in the form of recorded semi-structured focus groups were chosen as the most appropriate tool to explore the views of the team. The questions (referred to as the topic guide) were formulated after an extensive literature review and were then assessed for face and content validity by an expert panel. Willing eligible participants (n=26) were randomly assigned into three heterogenous focus groups with one group acting as the pilot study. The recorded data were then transcribed ad verbatim into raw text where participants were anonymised. The transcripts were analysed using the framework method whereby emerging categories and themes were devised. Quotations were then selected depending on their relevance to context of narrative text. Results: The framework analysis resulted in five main categories, namely: pharmacists as the expert reference point, ward availability, personal characteristics, attitudes towards potential clinical services and the link with the community. Key study outcomes were then highlighted as follows. Clinical pharmacists are considered as a valuable reference point for guidance in mixture compatibility and documentation issues. They are desired in the ward (including ward rounds) for their pharmaceutical expertise, especially in stock management and medication review. They are also believed to have a role in formulary management, principally in making protocols more lenient. They are required for patient counselling to increase compliance and to educate both patients and doctors alike on waste management. A missing link with the community in terms of hospital pharmaceutical services was acknowledged. Innovative concepts were also mentioned, including medication reviews on an outpatient basis. Conclusion: The general view of healthcare providers on the clinical pharmacist's role in palliative care was largely supportive and positive. This should encourage policy makers to introduce clinical pharmacy services within this setting. References and/or acknowledgements: 1. Hall P, Weaver L. Interdisciplinary education and teamwork: a long and winding road. Med Educ2001;35:867–75. No conflict of interest